Populating a multilingual ontology of proper names from open sources - Savary, Agata; Manicki, Leszek; Baron, Małgorzata (Journal of Language Modelling, 2013)
Even if proper names play a central role in natural language processing (NLP) applications they are still under-represented in lexicons, annotated corpora, and other resources dedicated to text processing. One of the main challenges is both the prevalence and the dynamicity of proper names. At the same time, large and regularly-updated knowledge sources containing partially-structured data, such as Wikipedia or GeoNames, are publicly available and contain large numbers of proper names. We present a method for a semi-automatic enrichment of Prolexbase, an existing multilingual ontology of proper names dedicated to natural language processing, with data extracted from these open sources in three languages: Polish, English and French. Fine-grained data extraction and integration procedures allow the user to enrich previous contents of Prolexbase with new incoming data. All data are manually validated and available under an open licence.